Childhood malnutrition within the indigenous Wayuú children of northern Colombia. Issue 6 (2nd June 2020) - Russell, Eric A.; Daza Atehortua, Cristhian; Attia, Suzanna L.; Genisca, Alicia E.; Palomino Rodriguez, Arnaldo; Headrick, Andrew; Solano, Lina; Camp, Elizabeth A.; Galvis, Ana María; Crouse, Heather L.; Thomas, James A.
ABSTRACT: Malnutrition contributes to nearly half of all preventable deaths in children under the age of five. While the burden of disease is heaviest in Sub-Saharan Africa, South, and Southeast Asia, malnutrition in Latin America remains high, especially within indigenous communities. This study evaluates the prevalence of malnutrition and its relationship with access to healthcare resources within 172 indigenous Wayuú communities in La Guajira, Colombia. Healthcare workers administered a health questionnaire and collected anthropometric measurements on all children 6 months to 5 years of age within the Wayuú households. These data were utilised to calculate the prevalence of acute malnutrition, stunting, and underweight. Of all surveyed Wayuú children, 22.9% and 18.3% met criteria for moderate and severe malnutrition, 33.4% and 28.1% met criteria for moderate and severe stunting, and 28.1% and 16.6% were moderately and severely underweight. Across all categories, malnourished children were older, less likely to have had a medical professional present at birth, less likely to have received medical care after birth, and more likely to have been born in a non-medical, community setting. The prevalence of malnutrition is much higher than national levels in Colombia. This population requires urgent assistance to address their disproportionately high rates of malnutrition.